Renal function in patients following a low carbohydrate diet for type 2 diabetes: a review of the literature and analysis of routine clinical data from a primary care service over 7 years. Issue 5 (22nd October 2021) - Unwin, David; Unwin, Jen; Crocombe, Dominic; Delon, Christine; Guess, Nicola; Wong, Christopher
Abstract : Supplemental Digital Content is available in the text Abstract : Purpose of review: People with T2 Diabetes (T2D) who follow a low carbohydrate diet (LCD) may increase their dietary protein intake. Dietary protein can modulate renal function so there is debate about its role in renal disease. There is concern that higher protein intakes may promote renal damage, and that LCDs themselves may impact on cardiovascular risk. We review the evidence around LCDs, renal and cardiovascular risk factors and compare to results obtained in a real-world, primary care setting. Recent findings: Chronic kidney disease (CKD) is a well-recognised microvascular complication of T2D caused in part by; chronically increased glomerular pressure, hyperfiltration, increased blood pressure and advanced glycation end products. Hyperglycemia can be seen as central to all of these factors. A LCD is an effective first step in its correction as we demonstrate in our real-world cohort. Summary: We found evidence that LCDs for people with T2D may improve many renal and cardiovascular risk factors. In our own LCD cohort of 143 patients with normal renal function or only mild CKD, over an average of 30 months the serum creatinine improved by a significant mean of 4.7 (14.9) μmol/L. What remains to be shown is the effect of the approach on people with T2D and moderate/severe CKD.